2021
DOI: 10.1093/jpp/rgaa023
|View full text |Cite
|
Sign up to set email alerts
|

Propolis from southeastern Brazil produced by Apis mellifera affects innate immunity by modulating cell marker expression, cytokine production and intracellular pathways in human monocytes

Abstract: Objectives Propolis is a bee-made product used for centuries due to its diverse biological properties, including its immunomodulatory action. This work aimed at investigating whether propolis may affect monocyte functions challenged with retinoic acid (RA), B subunit of Escherichia coli heat-labile enterotoxin (EtxB), human melanoma-associated antigen-1 (MAGE-1) and lipopolysaccharide (LPS). Methods Monocytes from healthy don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…The impaired interaction between CD80 and CD28 may lead lymphocytes to anergy or death, while the proper binding supports the activation of the Th1 profile, contributing to the antitumor immune response (Lahat et al, 2003;Mattern, Flad, Brade, Rietschel, & Ulmer, 1998;Wolk, Döcke, von Baehr, Volk, & Sabat, 2000). EEP enhanced CD80 expression induced by Escherichia coli enterotoxin B in human monocytes (Conte et al, 2021), what suggested that the effects of EEP + DTX on CD80 expression was due to DTX. In addition, this effect may also be due to the chemical composition of propolis, since another Brazilian sample-the red propolis-had an opposite effect on murine macrophages, inducing CD80 gene expression (Bueno-Silva et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The impaired interaction between CD80 and CD28 may lead lymphocytes to anergy or death, while the proper binding supports the activation of the Th1 profile, contributing to the antitumor immune response (Lahat et al, 2003;Mattern, Flad, Brade, Rietschel, & Ulmer, 1998;Wolk, Döcke, von Baehr, Volk, & Sabat, 2000). EEP enhanced CD80 expression induced by Escherichia coli enterotoxin B in human monocytes (Conte et al, 2021), what suggested that the effects of EEP + DTX on CD80 expression was due to DTX. In addition, this effect may also be due to the chemical composition of propolis, since another Brazilian sample-the red propolis-had an opposite effect on murine macrophages, inducing CD80 gene expression (Bueno-Silva et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory activity of propolis was shown to be independent from autophagy, since LC3 expression was not induced. In addition, propolis inhibited NF‐κB expression, downregulating monocyte inflammatory activity 123 . Even though the signaling pathways modulated in differentially polarized monocytes were not fully elucidated, propolis exerted an immunomodulatory activity oriented toward an anti‐inflammatory profile.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
“…Additionally, the authors demonstrated that cytokine production was dependent on TLR-4 and could be abolished by blocking TLR-4. 122 Conte et al, 123 demonstrating once again that it may favor an anti-inflammatory milieu. In LPS-treated T h 17 polarized cells, propolis decreased CD40 expression and sustained LPS-induced IL-6 production.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
See 2 more Smart Citations